SWOT ANALYSIS IN IMPROVING MARKETING STRATEGIES IN CIRCLE K GUNAWANGSA SURABAYA - Asmie Poniwatie; Indah Noviandari; RM Bramastyo Kusumo; Dio July Pratama (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This research is motivated by the development of a modern retail business which is increasingly spreading in various regions. The existence of increasingly fierce competition and increasingly sophisticated technological developments requires retail businesses to determine the strategy to be used. The main purpose of determining this strategy is so that modern retail businesses can see objectively the internal and external conditions of their business in an effort to compete with other modern retail businesses. This study aims to analyze how to determine the marketing strategy at Circle K Gunawangsa Surabaya. This research is a qualitative research with descriptive type. This research was conducted by collecting respondents using a questionnaire. This study uses SWOT analysis, the first step is to create IFAS and EFAS matrices by giving weights to find the total score of the IFAS and EFAS variables. The second step is to formulate the SO, WO, ST, and WT strategies. The results of this study indicate that Circle K Gunawangsa Surabaya is in Quadrant I with an aggressive strategy which means it shows an SO strategy where the company uses all strengths to seize and take advantage of opportunities as much as possible.